Deciphering the Interplay Between Lipid Metabolism and ExoU Activity in Pseudomonas aeruginosa-Induced Host Cell Death - Mahdi, Adam (Université d'Ottawa | University of Ottawa, 2025)
ExoU is a phospholipase A2 (PLA2)-like enzyme, expressed by the gram-negative bacterium Pseudomonas aeruginosa (P. aeruginosa). ExoU is associated with high mortality rates in patients because it induces high levels of cytotoxicity in host cells. Yet, the precise lipidomic changes it mediates in the host are unknown. To address this, I investigated the impact of ExoU on the viability of human THP-1 macrophages and NuLi epithelial cells. I found that exposure to P. aeruginosa expressing ExoU significantly reduces cell viability in THP-1 and NuLi cells compared to ExoU mutant strains. I validated these findings across various time points and multiplicities of infection and showed that ExoU-expressing P. aeruginosa induces higher levels of cell death. I then assessed the impact of inhibiting ExoU intracellular translocation to the inner leaflet of the plasma membrane by treating THP-1 cells with a late endosome inhibitor and showed that the treatment led to no change in cell viability. To determine the type of cell death induced by ExoU, I tested various pharmacological inhibitors to inhibit apoptosis, necroptosis, and ferroptosis. I demonstrated that while inhibiting apoptosis and necroptosis resulted in no change in viability, inhibiting ferroptosis at early time points transiently increased viability. To validate the role of ferroptosis, I treated cells with an inducer of ferroptosis; however, found no effect of the treatment on cell viability. Lastly, to elucidate the mechanism of ExoU’s activity, I performed a lipidomic assessment of glycerophosphocholines (GPCs) in THP-1 cells using high-performance liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI MS/MS). I found that exposure to P. aeruginosa-expressing ExoU increases the levels of lysophosphatidylcholines (LPCs), providing direct evidence of host cell membrane hydrolysis. Taken together, this thesis confirms ExoU’s PLA2 activity is associated with enhanced cytotoxicity.
Keywords: ExoU; Pseudomonas aeruginosa; Phospholipase A2; Lipidomics; Host Cell Death; Ferroptosis; Lysophosphatidylcholines (LPCs); Glycerophosphocholines (GPCs); LC-ESI-MS/MS (Liquid Chromatography-Electrospray Ionization-Tandem Mass Spectrometry); Bacterial Pathogenesis; Plasma Membrane Hydrolysis; Macrophages; Epithelial Cells; Type III Secretion System (T3SS); Host-Pathogen Interaction; Lipid Metabolism; Cell Death Pathways